Postaci disneyowskie we włoskich komiksach dla dorosłych a disneyizacja — przypadki Zerocalcare i Dr. Piry - Wielgosz, Aneta (Zagadnienia Rodzajów Literackich, 2025)
In this article, I analyze the use of characters from Disney comics and films for children in contemporary Italian comics for the adult public by two authors: Zerocalcare and Dr. Pira. I aim to describe the purposes of the use of these characters and to establish whether the comics in which they are used are an example of disneyization or an example of its criticism. In Italy, Disney has a particular cultural position, due to the enormous popularity of Disney comics and films. The use of Disney characters has a history in Italian underground comics. My analysis is based both on formal comics analysis and on a cultural approach to comics. I refer also to analysis of disneyization by Alan Bryman and Dario Bonifacio. As shown in the article, the common purpose for which comic authors use Disney characters is to establish a community of experience with their readers. They also use these characters for comical purposes, mostly based on the contrast between adult content and childlike form. In these comics there are some elements of disneyization (especially in Zerocalcare), however there are also elements of criticism towards Disney and disneyization. Zerocalcare openly criticizes values present in Disney’s comics and Dr. Pira resists disneyization by negating Disney’s language.